The Influence of the Filing System on Work Efficiency at the Beringin Police - Tobing, Annisa Nadya; Wulandari, Sri Eka; Silalahi, Flora Elisabeth (Journal Boas : Business, Economics, Accounting And Management, 2024)
An agency certainly needs a good archiving system to make it easier to find archives again. Archives are useful as evidence in written form. Archives in an agency have a very important role, maintaining security and confidentiality received or created by an agency will develop in accordance with the growth of the information itself. If the archiving system is implemented well, it will also have a good effect on work efficiency. This research is to determine the extent to which the archival system influences work efficiency at the Beringin Police. With archival system indicators, namely simplicity, archival procedures, economical, security, strategic and flexible. As well as indicators of work efficiency, namely the principle of planning, the principle of simplification, the principle of savings, the principle of elimination and the principle of merging. This research uses quantitative methods by collecting data through questionnaires addressed to Beringin Police staff or personnel. The population in the study was 30 people. Then the researcher took a sample, namely a saturated sample, where the entire population was used as a sample, namely staff or personnel totaling 30 people. The data was processed using validity tests, reliability tests, simple linear regression, analysis of the coefficient of determination and partial T test as data analysis.